The Distribution, Occupancy and Habitat Preference of Carnivores in Sarawak - Thaqifah Syaza, Binti Jailan (Universiti Malaysia Sarawak (UNIMAS), 2019)
Urbanization alongside the overwhelming demands for land and resources in Sarawak has forced Carnivora species into losing their natural habitat. In an attempt to thwart the risk of species extinction, gazettements of protected areas have been amplified to provide safe haven for wildlife. However, the knowledge in the capability of these isolated protected areas to withhold Carnivoran species are unclear. Camera trapping survey were carried out in 15 Totally Protected Areas (TPAs) throughout Sarawak resulting with 20 out of 25 Carnivora species recorded from a total of 42,712 camera trap effort. Highest Carnivora species richness were found to be in KNP with 52% while the lowest is in KWNP with 8%. Activity pattern of Carnivora alongside humans showed 16% activity overlap indicating avoidance behaviour. Carnivora occupancy and detection were found to be unexpectedly low within the sampled protected areas (psi <0.4; p <0.05). Modelling of multispecies occupancy with 22 sampled microhabitat covariates indicates that the percentages of canopy cover and the size of fallen logs are the best fit microhabitat model for Carnivora’s guild yet this differ strongly among single-species occupancy modelling results. Surprisingly, the size of protected areas showed no significant difference (p-value = 0.534) in influencing Carnivora species richness in Sarawak. However, Carnivora richness showed a decreasing pattern with an increase in the number of park visitors. Therefore, utilization and conservation of protected areas needs the consideration to minimize anthropogenic disturbances, identify and compartmentalize hotspot areas with high species richness within Totally Protected Areas for better conservation management. This is to ensure the viability and preservation of Carnivora and other species alike within a protected landscape in Sarawak.